Need for Bioequivalence Standards that Reflect the Clinical Importance of the Complex Pharmacokinetics of Paliperidone Palmitate Long-Acting Injectable Suspension - Ric M Procyshyn (Journal of Pharmacy & Pharmaceutical Sciences, 2020)
Paliperidone palmitate is a second generation antipsychotic, approved for the treatment of schizophrenia in the form of the long-acting injectable (LAI) products INVEGA SUSTENNA® (once monthly injection) and INVEGA TRINZA® (once every 3 months injection). Paliperidone palmitate dissolves slowly after deep intramuscular injection before being hydrolyzed to paliperidone and absorbed into the systemic circulation. The pharmacokinetic (PK) profile of the INVEGA SUSTENNA® formulation is biphasic, comprised of an initial relatively fast zero-order input, which allows rapid attainment of therapeutic concentrations without oral supplementation; and a subsequent maintained second-stage, first-order input, allowing for once monthly administration. Changes to the manufacturing processes can substantially alter the release characteristics of paliperidone palmitate LAI and consequently its PK profile. As an example, larger or smaller particle sizes of paliperidone palmitate can result in a delayed or accelerated release of paliperidone into the systemic circulation, respectively. Such changes are clinically relevant, as transient excursions above therapeutic plasma concentrations can be associated with an increased risk of adverse effects, including tachycardia, hypotension, QT prolongation, and extrapyramidal symptoms. Conversely, a delay in attaining therapeutic plasma concentrations of paliperidone on initiation of treatment, or a return to low plasma concentrations before the end of a dosing interval during repeated dosing, increases the risk of relapse. Given the integral relationship of the PK profile to the product’s clinical effects, it is important to have bioequivalence standards that reflect the complexity of the paliperidone palmitate LAI PK profile if one is to consider therapeutic equivalence based on simple bioequivalence testing. Although both the EMA and U.S. FDA have product-specific guidelines to determine bioequivalence, their requirements differ substantially. In Canada, no LAI product-specific bioequivalence guidance exists for multiphasic medication delivery systems, and the recently revised Comparative Bioavailability Standards: Formulations Used for Systemic Effects guidance applies only to oral and non-injectable formulations. We recommend that new Canadian standards be developed for multiphasic and biphasic intramuscular / subcutaneous (IM/SC) products, including paliperidone palmitate LAI products, because, similar to modified-release oral dosage forms, a different PK profile in modified-release IM/SC products can result in clinically meaningful differences in safety, efficacy, and tolerability. To ensure bioequivalence for both newly initiated and switch patients, this paper proposes bioequivalence standards that could be adopted in Canada that include two studies, a multiple-dose cross-over study, and a single-dose study with partial AUC metrics.